Treadmill walking exercise training and brain function in multiple sclerosis: Preliminary evidence setting the stage for a network-based approach to rehabilitation. Issue 1 (February 2018) - Sandroff, Brian M; Wylie, Glenn R; Sutton, Brad P; Johnson, Curtis L; DeLuca, John; Motl, Robert W
Exercise training has been identified as a highly promising approach for managing the cognitive consequences of multiple sclerosis (MS). This study represents a secondary analysis of resting-state functional connectivity (RSFC) magnetic resonance imaging data from a pilot treadmill walking exercise training intervention for improving cognitive processing speed (CPS) in MS. There were large intervention effects on RSFC between the thalamus and right superior frontal gyrus ( d = 1.92) and left medial frontal gyrus ( d = 1.70). There further were moderate-to-large intervention effects on CPS ( d = 0.72). Such preliminary data highlight FC within thalamocortical circuitry as a potential target for rehabilitation interventions for improving CPS in cognitively impaired individuals with MS.